Meningococcemia Masquerading as a Nonspecific Flu-Like Syndrome - Paula J. Watts; Natasha Fazel; Dmitriy Scherbak (Case Reports in Critical Care)
Neisseria meningitidis is a cause of bacterial meningitis and meningococcemia worldwide. Rarely, it causes invasive disease with significant lifelong sequela if survived. Early clinical recognition is key as meningococcemia is an easily treatable disease, yet mortality is 50% if it is left untreated. In this case review, we present a classic case of meningococcemia, with an atypical presentation.